Experimental Study of Indoor Thermal Environment and Ventilation Effectiveness in a Room with Ceiling Heating and Mechanical Ventilation - Wu Xiaozhou; Sun Xuefeng; Wang Fenghao (Zhileng xuebao)
Experimental studies of indoor thermal environment and ventilation effectiveness were performed in a room with low temperature radiant ceiling heating system combined with mixing ventilation system and displacement ventilation system. The results show that when radiant ceiling surface temperature ranges from 25 to 29 ℃, supply air temperature ranges from 15 to 19 ℃ and supply air flow rate equals 4.2h-1, the distribution of indoor thermal environmental parameters are relatively uniform, the indoor vertical air temperature differences are less than 1℃ and ventilation effectiveness is approximately 1.0 when low temperature radiant ceiling heating system is integrated with mixing ventilation system. The distribution of indoor thermal environmental parameters are relatively non-uniform, and the indoor vertical air temperature differences are large and up to 4℃ and ventilation effectiveness is approximately 1.1 when low temperature radiant ceiling heating system is integrated with displacement ventilation system.